ChemInform Abstract: Direct Catalytic Synthesis of Densely Substituted 3‐Formylpyrroles from Imines and 1, 4‐Ketoaldehydes. Issue 9 (March 2015) - Kumar, Indresh; Mir, Nisar A.; Ramaraju, Panduga; Singh, Deepika; Gupta, Vivek K.; Rajnikant, Rajnikant
Abstract A straightforward synthesis of densely substituted 3‐formylpyrroles in a modular fashion from 1, 4‐dicarbonyl compounds and aldimines under very mild conditions is developed.